Magnesium and nitrogen ratios in nutrient solutions and cucumber yield in closed hydroponic system - Parra-Terraza, Saúl; Angulo-Castro, Azareel; López-Rodas, Carlos Fabián; Retes-Manjarrez, Jesús Enrique (REVISTA TERRA LATINOAMERICANA, 2022)
Nutrient solutions with balance in ion ratios, proportions and concentrations optimize nutrient use ef f iciency and crop yield. The objective of this study is to evaluate under greenhouse conditions three percentage ratios Mg2 + (20, 30 and 40/100) and three of NO3- (40, 60 and 80/100) and their combination on the mineral composition, nutrient use ef f iciency (EUN) and the yield of cucumber (Cucumis sativus cv. Poinsett 76) developed in hydroponics. The experimental design was completely randomized with a factorial arrangement of 32 treatments and six replicates. The variables evaluated were mineral composition of leaves, stems and fruit, ef f iciency in the use of nutrients, and weight, diameter, length, number, and yield of fruit. The results were analyzed with the analysis of variance (ANOVA) and the means were compared with Tukey’s test (P ≤ 0.05). The superior yield was with the combination 20/100 Mg2+ and 60/100 NO3-, higher ratios of Mg2+ (40 and 60/100) and NO3- (80/100) reduced yield 33.4%, 30.7% and 20.6%, respectively, and decreased the ef f iciency of Mg and N, compared to 20/100 Mg2+ and 60/100 NO3-. The 60/100 Mg2+ ratio increased the nutrient concentration of Mg in the fruit, but decreased yield.